Grammatical Error Based On Surface Structure Taxonomy: A Case Study In Writing Narative Essay Economics Management’s Students At Universitas Nasional PASIM - Edi Purnama (Jurnal Sastra - Studi Ilmiah Sastra, 2022)
This research is aimed to find the result of students’ ability in writing English essay not only to know the problem in Taxonomy grammatical error but also to solve problem of writing on how to make students be able to write English grammatically. This research used Descriptive method. The research was conducted to discover students’ grammatical errors, classify them to the surface structure taxonomy proposed by Dulay,(1981) The data are taken from The data were taken from 1 classes of Universitas Nasional Pasim first semester 2021. There were (29) students Economics Management. It took us one semester to take the taken data from test of Mid, Final and Final assignments. The result of the research are: writing is divided into four categories including Omission (OM), Addition (AD), Misformation (MF) and Misordering (MO). The lowest ability in grammatical error is in Misformation (MF) for 67,1. It belongs to “Very Poor”. A case in point that the students have many difficulties in writing sentences which is grammatically in correct especially in A. Regulation such as: irregular type of words in wrong place. The second lowest of grammatical error is Ommision (OM) For 14,1% The students doing grammatical error in element that must exist in the sentences. The third lowest of grammatical error is Misordering (MS) for 9,7 % the students had difficulties in doing error due to the occurrence of element that doesn’t need to exist The fourth lowest of grammatical error is in Misordering (MO) 8,9 % students had difficulties in doing error due to the occurrence of element that doesn’t need to exist. It is marked by misordering for a morpheme or group of morpheme in the